ANALYZING THE EFFECT OF INDIAN OCEAN DIPOLE PHENOMENON TO THE ANOMALIES DISTRIBUTION OF SEA SURFACE TEMPERATURE IN WEST SUMATERA - Azuga, Nabila Afifah; Galib, Musrifin; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
The waters of West Sumatera that face directly into Indian Ocean is strongly influenced by Indian Ocean Dipole (IOD) phenomenon which caused an anomaly of sea surface temperature (SST) and affect rainfall intensity in the West Sumatera Province. This research was aimed to know the effect of IOD on the distribution and anomaly of SST and rainfall intensity in West Sumatera. Data processing methods in this research is using statistical and descriptive. The data used in this research are NOAA OI-SST, Dipole Mode Index (DMI), and rainfall data from BKMG. The results showed that IOD positive occured in October 2018 and the IOD negative occured in July 2016. During the positive IOD, SST distribution values were 28 ˚C – 28,8 ˚C and SST anomaly values were ​​-1,2 to -0,4, in the negative phase the distribution of SST values were 29,8 ˚C – 30,35 ˚C and the SST anomaly values were 0,15 to 0,7. The rainfall intensity during positive IOD phase is 157 mm/month and during negative IOD phase is 525 mm/month.